Determinant of Sustainable Entrepreneurial Intention : Mediating Role of Entrepreneurial Self-Efficacy - Andriyati, Rizka; Wardani, Dewi Kusuma; Setyowibowo, Feri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to analyze the effect of entrepreneurial education and sustainability orientation in influencing sustainable entrepreneurial intention by testing the mediating effect of entrepreneurial self-efficacy in predicting sustainable entrepreneurial intention. This study used a quantitative approach with 306 UNNES and UNS economics education students’ years of 2020 and 2021 as samples. Data was obtained by distributing an online questionnaire (Google Form). Data was analyzed using the SEM-PLS technique. The analysis’s results show that there is a significant positive effect between entrepreneurial education and sustainability on entrepreneurial self-efficacy. Entrepreneurial self-efficacy can mediate the relationship between entrepreneurial education and sustainability orientation in terms of sustainable entrepreneurial intentions. The findings also confirm that sustainable entrepreneurial intention can be formed through the formation of cognition stimulated when students take entrepreneurial education and individual personalities, which can be reviewed from a sustainability orientation.